Analysing factors that influence eBidding adoption in Malaysian public sector - Zulkifli, Megat Shariffudin; Said, Mohd Fuaad; Han, Chun Kwong; Choo, Wei Chong (Universiti Putra Malaysia Press, 2015)
This study analysed the use of eBidding system by Malaysian government agencies, which, despite its obvious benefits in cutting down red-tape and lessening workloads among the agencies officials, is plagued by low usage. As such, the objectives of the study are to examine the factors that affect system utilisation by Malaysian public sector procuring officials and to understand their behavior toward adopting the eBidding system. A self-administrated questionnaire was utilised and responses from 150 officers from various Malaysian government ministries were gathered and evaluated using structural Equation Modelling (SEM). The findings indicate that performance expectancy, effort expectancy, social influence, facilitating conditions and information quality significantly influence the adoption behaviour toward eBidding. Satisfaction, on the other hand, is concluded to have a mediating influence on the relationships between system quality, information quality and service quality with eBidding adoption. Given the significant impact of the behavioural factors of officials in eBidding adoption and role satisfaction, organisational administrators and managers can introduce key changes in the workplace to increase satisfaction among those using the eBidding system.